Propolis – therapeutic properties and application in modern medicine: A review - Florek, Julia; Dybiak, Paulina; Bartoszek, Mateusz; Grzegorzak, Erwin; Krawczyk, Oliwia; Minas , Jakub; Morawiec, Adrian; Słoma, Paweł; Pelczar, Rafał; Grodzki, Mikołaj; et al. (Quality in Sport, 2026)
Background. Propolis (bee glue) is a natural resinous substance collected by honeybees, utilized since antiquity for its healing properties. Modern medicine increasingly employs this raw material as a complement to conventional therapies in the treatment of infections, metabolic diseases, and oral cavity disorders. Aim. The aim of this study is to review the current scientific literature regarding the chemical composition, pharmacological properties, and clinical applications of propolis, with particular emphasis on its antimicrobial, metabolic, and neuroprotective activities. Material and methods. A review of literature from 2000–2023 was conducted using PubMed, Scopus, and Google Scholar databases. In vitro, in vivo, and clinical studies regarding the biological activity of propolis were analyzed. Results. Propolis exhibits a broad spectrum of activity: bactericidal (including against drug-resistant strains and biofilms), antiviral (e.g., HSV, SARS-CoV-2), antifungal, and regenerative. New reports confirm its efficacy in dentistry (caries, periodontitis), glycemic control in type 2 diabetes, and its neuroprotective potential in neurodegenerative diseases. Conclusions. Propolis represents a promising raw material in integrative medicine. Its multidirectional action, combined with relatively low toxicity, justifies further clinical research and standardization efforts.